Climate change scenario simulations over Eritrea by using a fine resolution limited area climate model : temperature and moisture sensitivity - Rautenbach, C.J. de W. (Cornelis Johannes de Wet) (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2007.